Alexandria: hub of the Hellenistic World - Schließer, Benjamin; Rüggemeier, Jan; Kraus, Thomas J.; Frey, Jörg; Herrmann, Daniel (Wissenschaftliche Untersuchungen zum Neuen Testament, 2021)
Cover -- Titel -- Table of Contents -- Preface -- Jan Rüggemeier - Alexandria: Hub of the Hellenistic World. Introduction -- 1. Alexandria as a Multidimensional Hub -- 2. Urban Encounters and the Fragility of Alexandria's Multiculturalism -- 3. The Outline and Rationale of this Volume -- I. The City -- Gregory E. Sterling - "The Largest and Most Important" Part of Egypt: Alexandria according to Strabo -- 1. Strabo's Descriptions of Cities -- 2. Strabo's Description of Alexandria -- 3. Significant Omissions -- 4. Conclusions -- Appendix: Strabo 17.1.6-10 -- Balbina Bäbler - Whose "Glory of Alexandria"? Monuments, Identities, and the Eye of the Beholder -- 1. Introduction -- 2. Written Sources and Material Remains -- 3. Mouseion and Library: Fortress of Greekness or Multicultural University? -- 4. Places of Paideia in Alexandria: How Jews Became from Shareholders to Objects -- 5. Conclusion -- Barbara Schmitz - Alexandria: What Does the So-Called Letter of Aristeas Tell Us about Alexandria? -- 1. "The First City of the Civilized World" (Diodorus 17.52.5) -- 2. "Alexandria" in the Letter of Aristeas -- 3. Comparing Alexandria with Jerusalem and Judea in the Letter of Aristeas -- 4. Alexandria and Jerusalem -- Christina Harker - Religious Violence and the Library of Alexandria -- 1. "The Muses' Bird-Cage" -- 2. "They Are Pernicious and Ought to Be Destroyed" -- 3. "They Reckoned Their Sacrilege and Impiety a Thing to Glory in" -- 4. "A Shameful Memory, Let It Burn" -- 5. Conclusion -- Maria Sokolskaya - Was Demetrius of Phalerum the Founder of the Alexandrian Library? -- 1. The Sources and Their Value -- 2. The Ptolemeans, Alexandria, and Athens -- 3. The Role of Jewish Studies -- 4. Why Demetrius? -- II. Egyptian and Hellenistic Identities.